Pengaruh Reliability, Tangible, Responsiveness, Assurance dan Empathy terhadap Customer Loyalty yang Dimediasi Customer Satisfaction pada Pemilik Kendaraan Bermotor Listrik di Indonesia - Lady; Bastanta Sebayang (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
As economic, business, and social activities require rapid mobility of people and resources, transportation has become a very important necessity. Although the sales of electric motors are not as big as conventional motors, the demand for them continues to grow. For a company to continue running, it needs customers who are loyal to the company. The purpose of this study was to examine the satisfied customer is have a good impact on customer loyalty. Researchers chose reliability, tangible, responsiveness, assurance and empathy variables as independent variables, customer loyalty as the dependent variable, and customer satisfaction as the mediating variable. The results showed that: 1) There is a direct influence with significant positive results on Reliability, Tangible, Responsiveness, Assurance and Empathy on Customer Loyalty. 2) There is an indirect effect with significant positive results on Reliability, Tangible, Responsiveness, Assurance, and Empathy on Customer Loyalty which is mediated by Customer Satisfaction.